Nipple Areola Complex Reconstruction With the "Half-Dome" Technique Following Implant-Based Breast Reconstruction. Issue 6 (June 2019) - Chen, Wendy; Fishman, Jordan E.; de la Cruz, Carolyn
Abstract : Background: No single technique for nipple areola reconstruction best fits every patient and clinical scenario. Many techniques fail to provide long-term projection. One especially challenging cohort are those patients who have undergone bilateral implant-based reconstruction. We developed a modification of the C-V flap reconstruction that increases projection in the bilateral, implant-based reconstruction patient. Methods: All patients who underwent nipple areola reconstruction following implant-based breast reconstruction and who had at least a 12-month follow-up visit were identified. Nipple projection was measured and compared between the 2 groups. Results: Forty patients were identified. Twelve patients, 23 nipples, underwent the standard C-V flap reconstruction. Twenty-eight patients, 59 nipples, underwent the half-dome modification. Average nipple projection following the half-dome technique is more than twice that of the C-V flap. Conclusions: The half-dome technique provides a useful alternative modification of the C-V flap in patients with implant-based reconstruction.